Analisis Potensi Pengembangan Usaha Roti XYZ Cabang Sepanjang, Sidoarjo - Kaila Tirta Tri Meifa; Sekar Ayu Wulandari; Taufiq Rahman Humaidi; Dini Nafisatul Mutmainah (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
XYZ Bakery, Sepanjang, is a micro, small, and medium enterprise (MSME) that has operated since 2004. However, its business development has been constrained by limited digital marketing, financial record-keeping, legal compliance, production equipment maintenance, and waste management. This study aims to analyze the business feasibility from non-financial and financial perspectives and to formulate development strategies using SWOT analysis. A mixed-methods approach with a parallel convergent design was employed by collecting primary and secondary data simultaneously. The non-financial analysis covered market and marketing, technical, environmental, legal, and human resource aspects, while the financial analysis applied the Break-Even Point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C Ratio), and Payback Period (PBP). The results showed that the business was highly feasible from both perspectives. It generated an NPV of IDR 1,886,198, an IRR of 176.33%, a B/C Ratio of 1.52, and a PBP of 0.72 years. The IFE and EFE matrix analyses placed the business in Quadrant V (Hold and Maintain). Therefore, market penetration, product development, digital marketing optimization, product innovation, and operational efficiency are recommended to support sustainable business growth